The influence of management support, training procedure and training environment on job performance among student in Malaysia Army Training Institutions - Azizi, Mohd Ariff (2013)
This study was conducted to gain view on the issue of the enhancement of job performance among trainee in Malaysian Army Training institution. The objective of this study is to determine the relationship between training procedure, training environment and management support and enhancement of job performance. Thus the researcher carried out his responsibility and took the opportunity to study the factors that influencing the enhancement of job performance among student attended course in selected Malaysian Army Training institution. There are three main factors identify that influence in job performance namely training procedure, training environment and management support. These three factors will be studied whether it has the influence the job performance in Malaysian Army training institution. This study is a descriptive study to find out the influence variable that related to enhancement of job performance. The study was conducted to find out the influence variable in training procedure, training environment and management support with job performance of student attended training conducted in IPDA and PULADA. The collected data will be analyzed by Statistical Package for Social Science version (SPSS) 20.0. There was 153 respondents selected and all of them give the feedback. The reason how the researcher manage to get full feedback is due to the connection and good cooperation among the staff, student and researcher. The finding from the coefficient result describing to the three predictor of the job performance in training institution through the standardized coefficients beta indicating that the predictor of management support with the significant level .333 was the highest amongst the three predictors. Training Procedure is the second highest with a less significant level .146 and for the training environment predictors data results show that the predictors is not significant with the value of .009. The finding of this study is benefited to the management, training institution and the soldiers attending the course. The finding will assist the top management to know the best way to conduct the training in training institution